2014
DOI: 10.1038/leu.2014.345
|View full text |Cite
|
Sign up to set email alerts
|

The IL-15 cytokine system provides growth and survival signals in Hodgkin lymphoma and enhances the inflammatory phenotype of HRS cells

Abstract: Gene expression profiles of KM-H2 cells were determined at 0, 4, 10 and 24 hours of rhIL-15 treatment and normalized to profiles of PBS-treated KM-H2 cells that were analyzed in parallel to control for expression changes induced by growth in cell culture per se. This approach identified a specific set of genes that showed a significant regulation by rhIL-15 at the respective time points, with 43 genes being differentially expressed at 24 hours (with a fold change of at least log2 0.75 ; Supplementary Table 2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…We also observed an IL15 signaling signature in cHL-Th cells (Fig. 1C) which supports the finding that HRS cells secrete IL15 (18).…”
Section: Characterizing Chl-infiltrating T Cells By Gene Expression Psupporting
confidence: 89%
See 1 more Smart Citation
“…We also observed an IL15 signaling signature in cHL-Th cells (Fig. 1C) which supports the finding that HRS cells secrete IL15 (18).…”
Section: Characterizing Chl-infiltrating T Cells By Gene Expression Psupporting
confidence: 89%
“…are enriched in cHL-Th cells. Indeed, these factors can be expressed by HRS cells and may also be expressed by other sources in the micromilieu (17,18,30). Our analysis confirms that these factors influence gene expression in infiltrating Th cells.…”
Section: Purinergic Signaling In Chlsupporting
confidence: 78%
“…IL-15 remains a surprising evasion mechanism in cHL due to its expected role in the differentiation and survival of NK cells ( 27 ). Ullrich et al found that cHL cell lines upregulate IL-15 and corresponding receptors, demonstrating that RS cells utilize IL-15 for growth and apoptosis resistance in an autocrine fashion, thereby competing with NK cells ( 68 ).…”
Section: Chl Mechanisms For Nk Cell Inhibitionmentioning
confidence: 99%
“…Experimental evidence shows that instant coffee protected lymphoma cells in animals from DNA damage and from gamma radiation in vitro [ 51 , 52 ]. In addition, the consumption of coffee may also be correlated with lower circulating levels of inflammatory markers, including chemokines, cytokines, and the basic fibroblast growth factor (FGF-2), which has been linked to lymphoma pathogenesis [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%